Pengujian Efektifitas Betadine, SoS, dan Hand Sanitizer, sebagai Antimikroba (Staphylococcus Aureus) - Kayla Khairatifah Zalianti; Ardi Mustakim (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2025)
Staphylococcus Aereus is a common us of skin and soft tissue infection. The aim of study was to evaluate the effectivaness of Betadine solution, Sos, and hand sanitizer as antimicrobial agent against S. Aereus. The study used a laboratory based experimental design, Where S. aereus was exposed to paper discs soaked in betadine, SOS, and hand sanitizer, the betadine disc showed a more significant antimicrobial effect than other This study shows that betadine is more effective than the others. Testing is carried out using the diffusion method where paper discs that have been soaked in antimicrobial substances are attached to the surface of agar media that has grown bacteria. In this way, a clear zone will be visible surrounding the disc paper as a sign of the microbe's sensitivity to the antimicrobial.